Ethnoastronomy-The Baduy agricultural calendar and prediction of environmental perturbations - JOHAN ISKANDAR; BUDIAWATI S. ISKANDAR (Society for Indonesian Biodiversity, 2016)
Iskandar J, Iskandar BS 2016. Ethnoastronomy-The Baduy agricultural calendar and prediction of environmental perturbations. Biodiversitas 17: 694-703. In the past, the village farmers of Java and other islands owned extensive the traditional ecological knowledge (TEK) on climate or pranata mangsa. It had culturally practiced as guidance to various agricultural activities, such as planting rice which is considered and fixed with dynamic climate conditions. Nowadays, however, the pranata mangsa has eroded and neglected by the majority irrigated rice (sawah) farmers. Unlike the sawah farmers, the Baduy people have culturally maintained the pranata mangsa (called by Baduy as pananggalan) for annual practicing the swidden farming (ngahuma). This paper discusses the way in which cultural practices of Baduy swidden farming based on traditional calendar. Method used in this study qualitative which is based on ethnoecology or ethnoastronomy approach. The result of study shows that the Baduy rice farming cycle isfixed annually with reference to an agricultural calendar. It has slightly affected by the various environmental perturbations, because the Baduy people have developed some strategies, such as by organizing the traditional calendar and applying the traditional agroforestry that productions can be used for both subsistence and commercial purposes.